2018
DOI: 10.1002/wps.20568
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of trauma effects: putative role of epigenetic mechanisms

Abstract: This paper reviews the research evidence concerning the intergenerational transmission of trauma effects and the possible role of epigenetic mechanisms in this transmission. Two broad categories of epigenetically mediated effects are highlighted. The first involves developmentally programmed effects. These can result from the influence of the offspring's early environmental exposures, including postnatal maternal care as well as in utero exposure reflecting maternal stress during pregnancy. The second includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
227
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(262 citation statements)
references
References 210 publications
(244 reference statements)
3
227
0
6
Order By: Relevance
“…Genotypes may interact with environmental stressors and sources of support to contribute to a range of individual developmental trajectories (Ellis, Boyce, Belsky, Bakermans-Kranenburg, & Van Ijzendoorn, 2011;Del Giudice, Ellis, & Shirtcliff, 2011). There is also growing evidence from animal models that stress or trauma may affect offspring through epigenetic mechanisms (Yehuda & Lehrner, 2018) and research is also needed to examine these effects in humans and their relation to autonomic state regulation.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Genotypes may interact with environmental stressors and sources of support to contribute to a range of individual developmental trajectories (Ellis, Boyce, Belsky, Bakermans-Kranenburg, & Van Ijzendoorn, 2011;Del Giudice, Ellis, & Shirtcliff, 2011). There is also growing evidence from animal models that stress or trauma may affect offspring through epigenetic mechanisms (Yehuda & Lehrner, 2018) and research is also needed to examine these effects in humans and their relation to autonomic state regulation.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…The second, intergenerational effects of trauma , considers the effects of parental exposure to trauma on psychiatric outcomes in the next generation. These studies have, for example, started to identify variation in stress regulation in children of Holocaust survivors as well as war veterans, independent of the children’s direct exposure to significant life stressors 4 .…”
mentioning
confidence: 99%
“…Research on epigenetic changes in response to early life adversity indicates pathways between stress exposure and adult health and behavior disorders in animals as well as humans (Blaze & Roth, 2015;Gröger, Matas, Gos, Lesse, Poeggel et al, 2016;Lester, Conradt, & Marsit, 2016). Epigenetic changes also appear to be implicated in the transmission of adversity and their attending consequences across generations (Dias & Ressler, 2014;Franklin, Russig, Weiss, Gräff, Linder et al, 2010;Roth, Lubin, Funk, & Sweatt, 2009), as do harsh socioeconomic conditions (Ellis & Dietz, 2017) and historical trauma (Yehuda & Lehrner, 2018). Of equal importance, recent research has also identified multiple neurobiological (Feldman, 2017) and behavioral (Lieberman, Padron, Van Horn, & Harris, 2005) processes that promote resilience, providing evidence for the biological basis for the love and care that is essential for human and other mammalian offspring to develop and thrive.…”
mentioning
confidence: 99%